Reclamation of Used Edible Oil. II - MORIYA, Masafumi; FURUTA, Mitsunori; IWANAGA, Kazuto; UEDA, Takashi; YAWATA, Miho; TAKEDA, Osamu; TOTANI, Nagao; TAKADA, Mitsunobu; YAMAGUCHI, Ayako (Journal of Oleo Science, 2005)
Used edible oil recovered from the food industry in Japan amounts to a few hundred thousand tons annually. Some recovered oil of good quality is used as a fatty acid source, as feed oil, in paint, and so on, after a simple refining method, but the rest is burned or discarded despite a relatively low level of deterioration. In our previous paper, two reclamation methods were proposed for low-grade used edible oil having Gardner color≥11 to produce non-food industrial oil of Gardner color<7.  In the present study one of the methods mentioned above, refining with barium hydroxide followed by hydrogen peroxide bleaching, was improved to be practically feasible in existing facilities. In addition, the mechanism of successful reclamation was investigated. The results of the investigation suggested that barium hydroxide treatment of used edible oil rendered lipophilic proteins, amino acids, and other inhibitors of hydrogen peroxide bleaching, easily removable from the oil by washing with water and filtration through adsorbent. The oil thus obtained was bleached effectively down to Gardner color 4-6, and its odor was dramatically improved by hydrogen peroxide treatment.